68Ga-DOTA-TATE PET/CT for Molecular Imaging of Somatostatin Receptor Expression in Metastasizing Chordoma: Comparison With 18F-FDG. (April 2017) - Derlin, Thorsten; Sohns, Jan M.; Hueper, Katja
Abstract : Abstract: Chordoma is a rare slow-growing neoplasm of neuroectodermal origin, which frequently recurs after removal and has the potential to metastasize. We present the case of a 53-year-old man with metastasizing chordoma who underwent 18 F-FDG and 68 Ga-DOTA-TATE PET/CT for restaging of disease and for evaluation of targeted radionuclide therapy potential. On both 18 F-FDG and 68 Ga-DOTA-TATE PET scans, increased tracer accumulation was observed in chordoma metastases. Besides the increased glucose metabolism in chordoma, this case highlights the potential of 68 Ga-DOTA-TATE PET/CT for restaging of chordoma as well the option of targeted radionuclide therapy in this entity.